2017
DOI: 10.1371/journal.pone.0174429
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and interstrain transfer of prophage pp3 of Pseudomonas aeruginosa

Abstract: Prophages are major contributors to horizontal gene transfer and drive the evolution and diversification of bacteria. Here, we describe the characterization of a prophage element designated pp3 in the clinical Pseudomonas aeruginosa isolate PA1. pp3 spontaneously excises from the PA1 genome and circularizes at a very high frequency of 25%. pp3 is likely to be a defective prophage due to its inability to form plaques on P. aeruginosa indicator strains, and no phage particles could be detected in PA1 supernatant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In recent years, phage therapy has been shown as a promising alternative to conventional antibiotic therapy ( Kortright et al., 2019 ). We previously found that several new lytic phages show effective antimicrobial potential against A. baumannii ( Yang et al., 2019 ), P. aeruginosa ( Li et al., 2017 ), and K. pneumoniae ( Shi et al., 2020 ). However, the clinical application of a 12-phage cocktail on P. aeruginosa infected burn wounds showed poor results compared with 1% sulfadiazine silver ( Jault et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, phage therapy has been shown as a promising alternative to conventional antibiotic therapy ( Kortright et al., 2019 ). We previously found that several new lytic phages show effective antimicrobial potential against A. baumannii ( Yang et al., 2019 ), P. aeruginosa ( Li et al., 2017 ), and K. pneumoniae ( Shi et al., 2020 ). However, the clinical application of a 12-phage cocktail on P. aeruginosa infected burn wounds showed poor results compared with 1% sulfadiazine silver ( Jault et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The obtained PCR fragment was cloned into the KpnI/PstI sites of plasmid pUCP24 ( West et al, 1994 ), resulting in pUCP wzy . Construct pUCP wzy was then electroporated into PA1RG to obtain the complementary strain PA1RG/ wzy as described previously ( Li et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several groups proposed and applied AMPs and other novel agents to treat and control the infection of P. aeruginosa and other similar pathogens [25,37,38]. More attention should be paid on the relationship between the bactericidal effects, quorum sensing system, and T3SS and their functions in bacterial infection.…”
Section: Discussionmentioning
confidence: 99%